America's Game in the Wild-Card Era: From Strike to Pandemic - Soderholm-Difatte, Bryan (Rowman & Littlefield Publishers, 2021)
A 2022 Choice Reviews Outstanding Academic Title "Baseball fans actively following the sport in the 1990s and 2000s will greatly appreciate this fantastic book and its detailed insight." —Library Journal Major League Baseball has had a long and storied history, but perhaps no era has been as competitive and unpredictable as the past 25 years, with an expanded postseason making for an unexpected and entertaining end to each season. In America’s Game in the Wild-Card Era: From Strike to Pandemic, Bryan Soderholm-Difatte provides a compelling examination of Major League Baseball since the 1994 players’ strike. He reveals how the last quarter century has been the most dynamic in MLB history and argues that bringing wild-card teams and the division-series round into the postseason mix have fundamentally changed how dynasties should be perceived. Following the major storylines for all 30 teams, along with the division races and state of dynasties over the past 25 years, America’s Game in the Wild-Card Era is a captivating look into a new age of baseball. America’s Game in the Wild-Card Era, together with Soderholm-Difatte’s America’s Game, Tumultuous Times in America’s Game, and The Reshaping of America’s Game, form the author’s complete, definitive history of Major League Baseball.